Robust method of estimating of odd ratios in case-control association studies - Paul, Manju Mary; Rai, Anil (The Indian Journal of Agricultural Sciences, 2020)
In case-control studies, association of a disease with a genetic trait can be studied in terms of Single Nucleotide Polymorphisms (SNP). Prospective and retrospective likelihoods are the two common approaches used to study this association. In this paper, a method based on Preliminary test, has been proposed, which is efficient than prospective approach by exploiting model assumptions of Hardy Weinberg Equilibrium (HWE) and robust against failure of model assumptions as compared to retrospective approach (2015-16). In this proposed approach, a Preliminary Test Estimator (PTE) has been suggested based on both prospective and retrospective approach for estimating of association of a disease with genetic marker. The proposed PTE has been empirically evaluated through a simulation study. The Preliminary Test Estimator developed was found to be robust against the deviation from HWE.